Justification of the Crank Tedder Parameters for Mineral Fertilizers - Sayakhat Nukeshev; Kairat Yeskhozhin; Yerzhan Akhmetov; Boris Gorbunov; Dinara Kossatbekova; Khozhakeldi Tanbayev; Adilet Sugirbay; Kaldybek Tleumbetov (AgriEngineering)
The aim of the research was to reduce the irregularity of mineral fertilizer granule flow by developing a tedder-vaulting breaker that prevents the formation of vaults over the sowing windows of the seeder hopper. Existing dosing devices for mineral fertilizers do not provide stable application of the required doses of mineral fertilizers due to vaulting as well as accumulation and sticking of fertilizers in hoppers. In order to achieve a stable and precise metering of high fertilizer doses, a crank tedder is suggested to be mounted inside the hopper. Its function is to break the constantly appearing dynamic vaults above the sowing windows and to crush the fertilizer clods, i.e., to provide the fertilizer sowing units with a continuous flow of material. Theoretical studies were carried out using methods of classical and applied mechanics, special sections of higher mathematics. The following optimal parameters were established: the tedder blade width 0.05–0.09 m, the radius of the elbow 0.028–0.034 m, the blade installation angle 23–27°, and the kinematic mode of the tedder k = 1.5–1.9. Experimental studies have shown that the use of a crank tedder provides a stable flow of mineral fertilizer granules through sowing windows and reduces the sowing unevenness between seeding units by 12–15% and sowing instability by 7–10%. At the same time, the degree of damage to granules of 1–5 mm size is insignificant and is within 2.8–3.5%.